AUDIT COMMITTEES IN ACTION: MODERATING EARNINGS MANAGEMENT STRATEGIES DURING FINANCIAL DISTRESS - Maulina Dyah Permatasari; Dian Sulistyorini Wulandari; Imamudin (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2025)
This study aims to analyze the effect of financial distress on earnings management with audit committee effectiveness as a moderating variable. The research data were derived from annual reports of non-financial companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period, selected using purposive sampling. The analysis method employed was panel regression using the Panel Least Squares (PLS) approach with a moderation test. The results indicate that financial distress has a negative and marginally significant effect on earnings management. However, when the interaction variable between financial distress and the audit committee is introduced, the results show that the audit committee strengthens the relationship between distress and earnings management. This suggests that the existence of audit committees in some firms does not necessarily function effectively to curb managerial opportunism, particularly under financial pressure. These findings provide crucial implications for policymakers and practitioners to enhance the quality and independence of audit committees in corporate governance practices.